Long-term survival following multimodal therapy for lung cancer with hepatic metastasis: a case report - Junjun, Zhao; Jiandong, Zhang; Lingjun, Dong; Guangmao, Yu; Chu, Zhang (Frontiers in Oncology, 2025)
BackgroundThe liver serves as a predominant metastatic site in advanced lung cancer, with patients developing hepatic metastases demonstrating particularly dismal prognosis and a median survival of approximately 5 months. Currently, no consensus has been established regarding optimal therapeutic strategies for lung cancer with liver metastases.Case presentationA patient with advanced lung cancer and oligometastatic liver metastases achieved significant tumor regression in both pulmonary and hepatic lesions following combined immunotherapy and chemotherapy. Subsequent radiofrequency ablation was performed for the liver metastasis, while surgical resection of the primary lung lesion resulted in pathological complete response (pCR). The patient has maintained long-term survival without evidence of disease recurrence.ConclusionsFor patients with advanced lung cancer and oligometastatic liver metastases demonstrating favorable response to combined immunotherapy and chemotherapy, consolidative surgical resection with adjunctive liver-directed local therapy may be considered, potentially conferring long-term survival benefits.